2016
DOI: 10.1186/s40536-016-0034-2
|View full text |Cite
|
Sign up to set email alerts
|

Proficient beyond borders: assessing non-native speakers in a native speakers’ framework

Abstract: The popularity and relevance of the English language has made foreign language education a mainstream endeavor around the globe (Dixon et al. 2012;Hu 2007). English language proficiency is considered a basic skill (Cha and Ham 2008;Graddol 2006) that students from different language backgrounds are expected to demonstrate, regardless of whether they are native speakers or non-native speakers. This holds true for all dimensions of language proficiency, however, the comprehension of written texts is one of the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Therefore, there is a need to further explore the role of DST in multilingual contexts, with the overarching goal of developing students' STEM-A disciplinary literacy in English. This need has emerged from problems related to students' language development (Anderson et al 2018) exacerbated by the increasing role of English in STEM areas (Plo-Alastrué et al 2015) as well as the economic divide between EFL and non-EFL speakers (Fleckenstein et al 2016). Previous research has shown a positive impact of DST in teaching astronomy (Ruddell et al 2016;Zellner 2018).…”
Section: Digital Storytelling and Science Disciplinary Literacy Develmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there is a need to further explore the role of DST in multilingual contexts, with the overarching goal of developing students' STEM-A disciplinary literacy in English. This need has emerged from problems related to students' language development (Anderson et al 2018) exacerbated by the increasing role of English in STEM areas (Plo-Alastrué et al 2015) as well as the economic divide between EFL and non-EFL speakers (Fleckenstein et al 2016). Previous research has shown a positive impact of DST in teaching astronomy (Ruddell et al 2016;Zellner 2018).…”
Section: Digital Storytelling and Science Disciplinary Literacy Develmentioning
confidence: 99%
“…Whereas reported educational statistics show a gap between non-native (EFL) and native (non-EFL) English speakers' literacy and numeracy test performance (Department of the Prime Minister and Cabinet 2018; National Assessment Program 2015; The Nation's Report Card 2015), recent research in linguistics underscores the misleading nature of such comparisons. While native speakers as a group usually outperform non-native speakers (Somers 2017;Fleckenstein et al 2016), there is high intragroup variability (Dąbrowska 2019;Hulstijn 2019). EFL students' proficiency in social, economic and academic English literacy makes them competitive against native English speakers in the global job market (Fleckenstein et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The globalization of English provides the language with a global lingua franca and an international language diversifies (Xu, 2018). The spread of the English language around the globe is classified by the linguist Braj Kachru that is consisting of three concentric circles representing different ways in which the language is acquired and used by people in different countries as represented in Figure 1 (Fleckenstein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Open Journal of Modern Linguistics,10,[459][460][461][462][463][464][465][466][467] https://doi.org/10.4236/ojml.2020.105027 Open Journal of Modern Linguistics different contexts (Savignon, 2017). However, English language teaching is looking for new approaches to address the range and level of English proficiency required for participation in today's global community (Fleckenstein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%